Transparency in product design: investigating design intentions and consumers' interpretations. (3rd October 2018) - Cheng, Peiyao; Mugge, Ruth; de Bont, Cees
ABSTRACT: Transparency is used in product design across various product categories. Because of the physical property of letting light go through, transparency can create unique visual styles. Transparency can also communicate additional information as a result of what is situated underneath the product cover, which prompts different consumers' interpretations. To support designers to use transparency effectively, this research aims to explore the use of transparency in product design to provide an overview of the design intentions of using transparency. Specifically, two studies were conducted. In Study 1, in-depth interviews with experienced designers ( N = 6) were conducted and the results revealed the overview of the following five design intentions of using transparency in product design: enrich visual appeal, enrich product experience, improve product usability, facilitate consumers' comprehension and demonstrate product functionality . The overview was further validated through consumer interviews ( N = 13) in Study 2.